Land Distribution Inequality and Farmer Poverty Vulnerability: Analyzing Land Gini Ratio and Poverty Severity Index Using the 2023 Agricultural Census - Marningot Situmorang (Agriculture Journal, 2026)
Land inequality remains a structural constraint on rural poverty reduction in Indonesia. This study examines the relationship between land distribution inequality and farmer poverty vulnerability using provincial data derived from the 2023 Agricultural Census (ST2023). Land inequality is measured using the Land Gini Ratio, while poverty vulnerability is assessed through the Poverty Severity Index. The analysis applies linear regression to evaluate the statistical association between variables. The results indicate a strong positive relationship (R² = 0.54, p = 0.002), suggesting that provinces with higher land inequality tend to exhibit deeper poverty severity among agricultural households. These findings highlight that land disparity is strongly associated with rural poverty vulnerability within the observed model. The study underscores the importance of equitable land distribution policies as part of inclusive rural development strategies.